2008
DOI: 10.1515/hf.2008.110
|View full text |Cite
|
Sign up to set email alerts
|

Towards novel wood-based materials: Chemical bonds between lignin-like model molecules and poly(furfuryl alcohol) studied by NMR

Abstract: Wood modification with furfuryl alcohol is a non-toxic alternative to conventional preservation treatments. A process in which furfuryl alcohol polymerises in situ was previously proposed for chemical modification of wood. In the present work, liquid model systems were investigated using compounds that resemble repeating units of lignin to verify whether chemical bonds form between the furfuryl alcohol polymer and wood. Using different NMR spectroscopic techniques we confirmed that these model compounds do for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 13 publications
6
63
1
Order By: Relevance
“…Two main processes for production of furfurylated wood have been developed for Kebony ASA: KebonyTM for hardwood modification and VisorWoodTM for softwood modification. NMR investigations with soluble lignin models indicated that the furan polymer grafts to lignin, supporting observations made with wood materials (Nordstierna et al 2008). Toxicity of furfuryl alcohol may constitute a drawback for this treatment, however, toxicity is strongly reduced after polymerisation.…”
Section: Furfurylation Treatmentsupporting
confidence: 71%
“…Two main processes for production of furfurylated wood have been developed for Kebony ASA: KebonyTM for hardwood modification and VisorWoodTM for softwood modification. NMR investigations with soluble lignin models indicated that the furan polymer grafts to lignin, supporting observations made with wood materials (Nordstierna et al 2008). Toxicity of furfuryl alcohol may constitute a drawback for this treatment, however, toxicity is strongly reduced after polymerisation.…”
Section: Furfurylation Treatmentsupporting
confidence: 71%
“…Even today, the question of whether furfurylation is a distinct chemical modification process remains unanswered. Some scientists believe that it comprises a chemical modification process, since the furfuryl alcohol polymer reacts with itself and possibly reacts with the lignin in the cell walls , Nordstierna et al 2008, Gérardin 2016, Li et al 2016. Thus, the furfuryl alcohol complexes are predominantly deposited in the wood cavities and cell walls (Fig.…”
Section: Furfurylationmentioning
confidence: 99%
“…The question of whether wood furfurylation is a true chemical modification of the cell wall remains unanswered by the scientific community. Some scientists believe that it comprises a chemical modification process, since the furfuryl alcohol polymer reacts with itself and possibly reacts with lignin in the cell walls (Nordstierma et al 2008;Lande et al 2008;Li et al 2016;Gérardin 2016). Hence, the furfuryl alcohol complexes are predominantly deposited in the wood cavities, and also in the cell walls (Fig.…”
Section: Furfurylationmentioning
confidence: 99%